2015 2nd International Symposium on Physics and Technology of Sensors (ISPTS) 2015
DOI: 10.1109/ispts.2015.7220113
|View full text |Cite
|
Sign up to set email alerts
|

Design and simulation of blocked blood vessel for early detection of heart diseases

Abstract: In this paper, we present two-dimensional modeling and simulation of blood vessel using COMSOL Multiphysics. The rationale behind this study is that mathematical modeling and numerical simulation can lead to better understanding of the phenomena involved in vascular diseases. This study assumes that the fluid is laminar, non-Newtonian, viscous and compressible and the arterial wall is elastic. Parameters of blood vessel were assigned to the wall and parameters for fat deposits to the blockages. Blood is an exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Wang et al [30] present haemodynamic metrics found in aortic dissection and quantitative indexes for optimal treatment planning. Moreover, Garje et al [31] observed numerical changes in vessels' blood flow and their growth due to an accumulation of cholesterol in coronary artery disease (CAD). Methods for observing geometry and blood flow through an abdominal aortic aneurism allow timely prediction of aneurism ruptures and are described by Canchi [32].…”
Section: Prior Aorta Simulation Methodsmentioning
confidence: 99%
“…Wang et al [30] present haemodynamic metrics found in aortic dissection and quantitative indexes for optimal treatment planning. Moreover, Garje et al [31] observed numerical changes in vessels' blood flow and their growth due to an accumulation of cholesterol in coronary artery disease (CAD). Methods for observing geometry and blood flow through an abdominal aortic aneurism allow timely prediction of aneurism ruptures and are described by Canchi [32].…”
Section: Prior Aorta Simulation Methodsmentioning
confidence: 99%
“…However, the simplicity of the model allows for further refinements in order to model different conditions including blood loss and haemorrhagic shock. A similar study [4] presented a two-dimensional modelling and simulation of blood vessel using COMSOL Multiphysics. The rationale behind the study is that mathematical modelling and numerical simulation can lead to better understanding of the phenomena involved in vascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…However, these observations were only predicted numerically. Garje et al [26] studied numerically the changes in blood flow vessels and the growth of a blockage, which is an occlusion of the coronary arteries typical of coronary artery disease (CAD), due to an accumulation of cholesterol. Their work was focused on the size and position of the blockage.…”
Section: Introductionmentioning
confidence: 99%